Rational application of the new European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) 2020 criteria for the diagnosis of coeliac disease - Enriqueta Román Riechmann; Gemma Castillejo de Villasante; M. Luz Cilleruelo Pascual; Ester Donat Aliaga; Isabel Polanco Allué; Félix Sánchez-Valverde; Carmen Ribes Koninckx (Elsevier, 2020)
Coeliac disease is a systemic immune-mediated disorder triggered by the ingestion of gluten, which is given in genetically predisposed subjects. It manifests with a wide variety of clinical symptoms, specific serological markers, HLA-DQ2/DQ8 haplotype, and enteropathy. The criteria followed for this have usually been those established by the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) since 1969. These criteria have advanced from the need of several intestinal biopsies to, thanks to the development of serological tests of high sensitivity and specificity, considering the enteropathy as one more element in this diagnosis and makes it possible to perform a diagnosis without the need of an intestinal biopsy in certain circumstances. The updated review of the 2012 criteria in 2019 provides new evidence on some aspects, such as the role of HLA, the diagnosis of asymptomatic patients, and the effectiveness of the serological markers. These aspects are reviewed in detail, with the aim of facilitating the rational application of the new 2020 criteria at all care levels. In this sense, Paediatric Primary Care is fundamental in the search for active cases and to perform a first serological study, being recommended that the diagnosis is always established by a Paediatric Gastroenterologist. Resumen: La enfermedad celíaca es un proceso sistémico de carácter inmunológico, desencadenado por el consumo de gluten, que se da en sujetos genéticamente predispuestos. Se expresa con una gran variedad de síntomas clínicos, marcadores serológicos específicos, haplotipo HLA-DQ2/DQ8 y enteropatía. El tratamiento consiste en eliminar de por vida el gluten de la dieta, por lo que es fundamental un diagnóstico adecuado. Los criterios seguidos para ello han sido habitualmente los establecidos por la European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) desde 1969. Estos criterios han ido evolucionando desde la necesidad de varias biopsias intestinales para el diagnóstico a, gracias al desarrollo de pruebas serológicas de alta sensibilidad y especificidad, considerar la enteropatía como un elemento más en este diagnóstico y posibilitar en determinadas circunstancias realizarlo sin necesidad de biopsia intestinal. La revisión actualizada en 2019 de los criterios 2012 aporta nueva evidencia sobre algunos aspectos, como el papel del HLA, el diagnóstico de los pacientes asintomáticos y la eficacia de los marcadores serológicos. Estos aspectos se revisan en detalle, con el objetivo de facilitar la aplicación de los nuevos criterios 2020 de una forma racional en todos los niveles asistenciales. En este sentido el pediatra de Atención Primaria es fundamental para la búsqueda activa de casos y realizar un primer estudio serológico, recomendándose que el diagnóstico sea siempre establecido por un pediatra gastroenterólogo.